Conference on Software Maintenance and Reengineering (CSMR'06) 2006
DOI: 10.1109/csmr.2006.36
|View full text |Cite
|
Sign up to set email alerts
|

Non-intrusive monitoring of software quality

Abstract: Measurement based software process improvement needs a non-intrusive approach to determine what and where improvement is needed without knowing anything about the methods and techniques used during project execution. Beside, it is necessary for obtaining successful business management, an accurate process behavior prediction. In order to obtain these results we proposed to use Statistical Process Control (SPC) tailored to the software process point of view. The paper proposes an appropriate SPC-Framework and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…However, although publications cite development process, measures are, in fact, related to pieces of the process and, thus, can be suitable for SPC. For instance, the measures effort and productivity [Card 1994;Baldassarre et al 2005;Wang and Li 2005;Boffoli 2006;Wang, Qing et al 2006;Chang and Chu 2008;Gou et al 2009;Tarhan and Demirors 2012;Vashisht 2014] are obtained for each task, activity or phase, producing data usefull to describe the process/subprocess performance. Considering that small processes are more suitable for SPC, some measures are related to parts of processes.…”
Section: Discussionmentioning
confidence: 99%
“…However, although publications cite development process, measures are, in fact, related to pieces of the process and, thus, can be suitable for SPC. For instance, the measures effort and productivity [Card 1994;Baldassarre et al 2005;Wang and Li 2005;Boffoli 2006;Wang, Qing et al 2006;Chang and Chu 2008;Gou et al 2009;Tarhan and Demirors 2012;Vashisht 2014] are obtained for each task, activity or phase, producing data usefull to describe the process/subprocess performance. Considering that small processes are more suitable for SPC, some measures are related to parts of processes.…”
Section: Discussionmentioning
confidence: 99%
“…Four of the publications considered relevant to the study describe the same approach applied in different contexts ( [39][40][41] [42]). This approach is the only one identified that deals with knowledge management practice to support process performance analysis.…”
Section: Search Stringmentioning
confidence: 99%
“…In each case, not only are there few cases of successful applications but they don't clearly illustrate the meaning of control charts and related indicators in the context of software process application. Given the above considerations, the aim of this work is to generalize and put together the experiences collected by the authors in previous studies on the use of Statistical Process Control in the software context (Baldassarre et al, 2004;Baldassarre et al, 2005;Caivano 2005;Boffoli, 2006;Baldassarre et al, 2008;Baldassarre et al, 2009) and present the resulting stepwise approach that: starting from stability tests, known in literature, selects the most suitable ones for software processes (tests set), reinterprets them from a software process perspective (tests interpretation) and suggest a recalculation strategy for tuning the SPC control limits. The paper is organized as follows: section 2 briefly presents SPC concepts and its peculiarities; section 3 discusses the main differences and lacks of SPC for software and presents the approach proposed by the authors; finally, in section 4 conclusions are drawn.…”
Section: Introductionmentioning
confidence: 99%